СТАНОВЛЕННЯ ТА РОЗВИТОК ІНСТИТУТУ ЕЛЕКТРОННОЇ ПОДАТКОВОЇ ПЕРЕВІРКИ СУБ’ЄКТІВ ГОСПОДАРЮВАННЯ В УКРАЇНІ - Dmytrenko, E.S. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2022)
The article clarifies the issue of the formation of electronic document management under the laws of Ukraine. Peculiarities and problems of providing electronic services to economic entities through the electronic office of the taxpayer are considered. Attention is paid to the ways in which the taxpayer interacts with the controlling authority by electronic means of communication. The essential features of the electronic tax audit, which is carried out based on the application of the business entity as a taxpayer, have been identified. The stages of introduction of electronic tax audits in Ukraine have been clarified. The procedure for providing electronic documents at the request of the controlling body by an economic entity that is a large taxpayer is considered. Emphasis is placed on the general requirements for the provision of electronic documents in electronic form by such taxpayers during the documentary audit. Based on the analysis of the legislation of Ukraine, it is concluded that it does not define the terms “electronic audit” and “electronic tax audit”. To solve this problem, it is proposed to add their definitions in Article 1 of the Law of Ukraine “On Auditing Financial Reporting and Auditing” and Article 14 of the Tax Code of Ukraine, as well as the author's definition of “electronic tax audit”. The analysis of changes in the legislation of Ukraine and the experience of the European Union member states clarifies the features and problems of using the standard audit file (SAF-T) in the electronic tax audit of taxpayers. Attention is drawn to the need to regulate the procedure for conducting electronic tax audits in legislation and to develop a Standard for conducting this type of audit. It is proposed to make other changes to the legislation of Ukraine to protect the rights of economic entities when providing them with electronic services in the field of taxation. REFERENCES